Penegakan Hukum Terhadap Kasus Tindak Pidana Pelaku Illegal Fishing - Budi Raharja (CV. Rayyan Dwi Bharata, 2025)
As a marine state, Indonesia has about 78% of its territory covered by sea waters to provide its fishermen in pursuing their happiness. Yet, the fact that owing to the illegal fishing by mostly undocumented foreign flag ships, Indonesian fishermen do not significantly deserve their prosperity whereas partly of their lives depending on the income from fish catching and in return, Indonesia suffered a loss of her annual financial income. For this reason, Indonesia government has issued the law No. 45/2009 concerning the Fishery and its Article 69 (4) provides the space of strict law enforcement to sink and burn the proven foreign illegal fishing ships. The problems raised are how the law enforcement and its impact in sinking and burning the foreign illegal fishing ships would be in line with the International Law of Sea. This article has revealed that law enforcement of sinking and burning the foreign ships is not only lawful but consistent as well with the mentioned law above and it does not bring up any legal effects to foreign countries as the foreign illegal fishing ships are sunk and burned within the territory of Indonesian economic exclusive zone as stipulated in the UNCLOS 1982.